Characteristics of Cross-Linked Oil Palm Starch' - Haryadi Haryadi; Chusnul Hidayat; Kapti Rahayu Kuswanto (Indonesian Association of Food Technologists, 1996)
Oil palm starch was cross-linked with 0.005-0.025% phosphorus oxychloride (POC1) in alkaline solution. The modified starches were analyzed for degree of substituÂ¬tion (DS), amylographic properties, swelling power, paste turbidity, and in vitro digestibility using porcine pancreatic a -amylase. The results suggested that the cross-linking procedure afforded modified starches with DS of 0.0134-0.0184. Increase in the use of POC13 reÂ¬sulted in a higher DS of the starch derivative. Starting at the use of 0.015% POC13 the DS tended to level off. Cross-linking caused the starch more stable to heat and shear, decreased the swelling power, and increased in the paste turbidity. The solubility and digestibility of starch with a DS of 0.0134 were slightly increased, while starches with higher DS were less soluble and less digestible.